Investigating the effect of echinacea extraction syrup on the outcomes of lower respiratory infections in patients with COVID-19: a randomized clinical trial study - Elham Kheirandish; Mehrsadat Mahdizadeh; Mousa Mahdizadeh; Fariba Rezaeitalab; Mahdi Yousefi; Seyedeh Sara Rezazadeh Shojaee (Virology Journal)
Abstract Introduction Many COVID-19 patients experience mild to severe symptoms, including respiratory system involvement. Different treatment instructions have been suggested for patients with COVID-19. Echinacea has known antiviral effects. However, there is still not enough evidence that it is effective in treating COVID-19. This study was conducted with the aim of determining the effect of Echinacea extract syrup on the outcomes of the lower respiratory tract in patients with COVID-19. Methods In this single-blind randomized controlled trial, 40 patients with COVID-19 who were inpatients in the hospitals of Mashhad University of Medical Sciences, Iran, were randomly selected and assigned to two equal control and experimental groups (n = 20). In addition to receiving routine care and treatment (oxygen supply, remdesivir, enoxaparin and heparin), the experimental group received 5 cubic centimeter (CC) of Imogen syrup three times a day for 5 days each. The control group only received routine care and treatment. The data were collected on the first, third and fifth days after hospitalization and were analyzed using descriptive and analytical tests in Statistical Package for the Social Sciences (SPSS). The significance level was set at p < 0.05. Results The mean white blood cell count in the experimental group after the intervention decreased significantly compared to that before the intervention (t = 0.434, p = 0.045, df = 19). Arterial oxygen pressure increased significantly in both the experimental group (t = 4.382, p = 0.000, df = 19) and control group (t = 3.239, p = 0.004, df = 19), however no statistical differences were observed between experimental and control groups after intervention. The level of lung involvement (p = 0.320) and cough symptoms (P = 0.347) were not significantly different between the experimental and control groups after the intervention. In addition, there were no significant differences between the experimental and control groups in terms of the mean oxygen saturation, temperature, and number of breaths per minute on the first, third, and fifth day (p > 0.05). Discussion The consumption of Echinacea extract syrup may not be able to improve the symptoms of acute lower respiratory tract infection in patients with COVID-19 with 3 daily doses for 5 days. More studies should be conducted to investigate the clinical effects of Echinacea extract in the treatment of patients with pulmonary complications. Trial Registration IRCT20130522013423N2.